Pharmacovigilance in epileptic patients using antiepileptic drugs Farmacovigilância em pacientes com epilepsia em uso de drogas antiepilépticas - Paulo Afonso Mei; Maria Augusta Montenegro; Marilisa M. Guerreiro; Carlos A.M. Guerreiro (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To investigate the occurrence of adverse effects of antiepileptic drugs (AED) in chronic epileptic patients in mono or polytherapy. METHOD: We evaluated consecutive patients that met the following inclusion criteria: age of 18 years or older, diagnosis of epilepsy for at least one year, stable dose of AED for at least three months. Patients were asked if they had any adverse event related to the AED. After that, they were interviewed according to a detailed semi-structure questionnaire. We also assessed specifically the adverse events in the last four weeks. The data were analyzed regarding the use of monotherapy x polytherapy, and the presence of probable depression (score >15) according to the Center for Epidemiologic Studies Depression Scale. RESULTS: Sixty-five patients were evaluated, 35 women, mean age 38.3 years; 35 patients were in use of monotherapy and 35 in polytherapy. Only 45 (69.2%) patients spontaneously reported adverse effects. After the formal questionnaire, 63 (97%) patients referred experiencing an adverse event (p<0.001). Seventeen men had adverse events, as opposed to 28 women (p=0.042). When the last four weeks were evaluated, patients with probable depression presented adverse events more frequently (p<0.0001). CONCLUSION: Our data suggest that adverse events are highly prevalent when a detailed questionnaire is applied and that depression may aggravate the number and intensity of side effects in patients using AEDs. OBJETIVO: Investigar a ocorrência de efeitos adversos das drogas antiepilépticas (DAE) em pacientes com epilepsia crônica tanto em mono quanto em politerapia. MÉTODO: Avaliamos consecutivamente os pacientes que preencheram os seguintes critérios de inclusão: idade igual ou superior a 18 anos, diagnóstico de epilepsia por no mínimo um ano, doses estáveis de DAE por no mínimo três meses. Os pacientes foram instados a responder espontaneamente sobre a presença de efeitos colaterais das DAE. Após isto, um questionário formal sobre eventos adversos foi aplicado. Também avaliamos especificamente a presença de queixas nas últimas quatro semanas. Os dados foram analisados levando-se em conta o uso de mono ou politerapia e a presença ou não de provável depressão (índice >15) segundo o CES-D. RESULTADOS: Sessenta e cinco pacientes foram avaliados, 35 mulheres, idade média 38,3 anos; 35 pacientes estavam em uso de monoterapia e 35 em politerapia. Somente 45 (69,2%) pacientes espontaneamente registraram a presença de efeitos adversos. Após o questionário formal, 63 (97%) pacientes tiveram queixas (p<0,001). Dezessete homens e 28 mulheres reportaram eventos adversos (p=0,042). Quando as últimas quatro semanas foram analisadas, os pacientes com provável depressão relataram mais freqüentemente a presença de efeitos adversos (p<0,0001). CONCLUSÃO: Nossos dados sugerem que efeitos adversos são altamente prevalentes quando um questionário detalhado é aplicado e que depressão pode agravar o número e a intensidade de eventos adversos em pacientes com epilepsia utilizando DAE.